Intangible Benefactors and the Contribution of Construal Level and Attitude Accessibility in Predicting Gratitude and Expansive Emotions - Jenae M. Nelson; Sarah A. Schnitker; Emily Williams; Jo-Ann Tsang (Religions, 2022)
We tested whether manipulating construal level would change the experience of gratitude or other expansive emotions (gratitude, awe, compassion) and negative emotions. We also examined whether construal level was correlated with the type of gratitude benefactor that participants spontaneously listed, focusing especially on God and non-theistic intangible benefactors compared to tangible human benefactors. We manipulated construal level in 265 U.S.-based CloudResearch participants to test preregistered hypotheses that high-level construals would elicit more examples of gratitude toward intangible benefactors and increase expansive emotions. We conducted additional exploratory analyses, investigating whether attitude accessibility of God as a benefactor was correlated with increases in expansive emotions. High construal level manipulation was associated with more frequently listing non-theistic intangible benefactors. Further, trait construal level predicted expansive emotions. Additionally, attitude accessibility of God as a benefactor was positively related to expansive emotions. We discuss future research possibilities to differentiate between gratitude toward tangible and intangible benefactors and the use of attitude accessibility as an implicit measure of benefactor importance.